Pengaruh Profesionalisme dan Kompetensi Amil terhadap Pengelolaan Zis pada Laznas PPPA Daarul Qur’an Sul-Sel - Ratnasari, Ratnasari; Masse, Rahman Ambo; Muslihati, Muslihati (Lembaga Yasin AlSys, 2024)
This research uses a quantitative type of research with a survey approach. The population in this study were donors or muzakki at LAZNAS PPPA Daarul Qur'an Sul-Sel. The sampling technique used purposive sampling technique by determining the number of samples using the Krejcie Morgan formula, so that a sample size of 108 respondents was obtained. The types of data used are primary and secondary data and data collection through distributing questionnaires. Data processing uses SPSS 21. Based on research results using the F test, the calculated F value is 5.928 > F table 3.08 with a probability value of 0.004 < 0.05. This means that the variables of professionalism and amil competence together have a positive and significant influence on the variables of zakat, infaq and alms management at LAZNAS PPPA Daarul Qur'an Sul-Sel. Based on the results of the partial test (t test) on the amil professionalism variable, the calculated t value was 2.867 > t table 1.982 with a significant value of 0.001 < 0.05 so that the amil professionalism variable had a positive and significant effect on the zakat, infaq and alms management variables at LAZNAS PPPA Daarul Qur'an Sul-Sel. Meanwhile, the competency variable does not have a positive and significant influence on the zakat, infaq and alms management variables at LAZNAS PPPA Daarul Qur'an Sul-Sel. This is proven by the calculated t test results of -0.739 < 1.982 with a significant value of 0.481 > 0.05.